Reduction of earth resistance by application of chemical and natural materials - Buba, Sani Dahiru (2012)
Earthing systems provide continuous and conductive electrical path to the ground for dissipation of fault currents, lightning transient charges and ensures the safety of humans against contact with energised circuits and systems. Earthing systems also provide a zero signal reference for electronic systems and ensures reliable operation of power system both under normal and fault conditions. Local and international earthing standards have recommended minimum values of earth resistance required for earthing systems to provide adequate protection. However, it is difficult to achieve low earth resistance in ordinary soil conditions due to variation of soil resistivity from one location to the other. Hence, the objective of this study is to determine the performance of chemical and natural materials for reduction of earth resistance of vertically installed earth electrodes. A combined experiment based on soil enhancement and electrode enhancement was conducted in UPM, Serdang, Selangor, Malaysia (Latitude 2.990 N, longitude 101.710 E). The experiment based on soil enhancement was installed by driving five earth electrodes made of solid copper into the soil to a depth of 1.4m separated at intervals of 3m from each other. Five circular trenches of dimension 0.2m wide by 0.15m deep were dug around each of the earth electrodes for placement of 10kg each of chemical materials such as sodium chloride, sodium thiosulphate, magnesium chloride, calcium chloride and calcium-magnesium carbonate (dolomite) in separate trenches. The experiment based on electrode enhancement was installed by drilling five holes with dimension of 0.13m diameter and 1.5m deep which were each filled with different natural materials such as palm kernel fibre, kenaf fibre, paddy dust (rice husk),bentonite and Sungai Besar Marine Clay and compacted. Five earth electrodes made of solid copper were driven at the centre of each hole to a depth of 1.4m. Another earth electrode was installed without any enhancement material around it as a reference. All copper earth electrodes used were of similar dimensions of 0.013m diameter and 1.5m length. For all 11 earthing installations, 0.1m length of the earth electrode was allowed above grade for clamping of earth resistance meter. Plastic earth chambers were placed on all earthing installations to serve as inspection boxes. Earth resistance measurement was conducted using 3-point fall of potential method on daily basis for a period of one year using a Megger Digital Earth Tester, model DET3TC. After 365 days, results of earth resistance measurements indicated that the earth resistances have reduced from their initial values by 78.30%, 74.65%, 68.61%,64.49%, and 29.16%, for sodium chloride, calcium chloride, magnesium chloride,sodium thiosulphate, and calcium-magnesium carbonate installations, respectively when compared to the reference installation. Similarly, earth resistance for bentonite,palm kernel fibre, Sungai Besar Marine Clay, kenaf fibre and paddy dust (rice husk) installations over the same period have reduced by 56.43%, 34.65%, 17.32%, 16.81% and 2.92%, respectively. It is concluded from the study that chemical materials are a better choice for reduction of earth resistance compared to natural materials. The cost of installing earthing systems with natural materials is averagely 65% cheaper than earthing systems with chemical materials. In terms of installation technique, earthing systems with chemical materials are easier to install as earthing systems with natural materials require more equipment and operators during the installation process. It is also easier and cheaper to maintain earthing systems with chemical materials. Considering the impact on environment, the study did not reveal any effect from the two installations as the grasses germinated at the same rate and maintained similar colour. The only discolouration of grass that was observed is specifically at water logged spots.